2016
DOI: 10.3389/fmars.2015.00117
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hydroxyl Radical Formation and Correlated Photoflocculation Process Using Degraded Wood Leachate as a CDOM Source

Abstract: In this study, we examined hydroxyl radical ( OH) formation with respect to photoreactivity of colored dissolved organic matter (CDOM), the Fenton reaction, and photoflocculation using leachate from decaying wood. The relationship between OH photoproduction rate and leachate optical properties (UV-visible absorption and fluorescence excitationemission matrices (EEMS)) was studied during irradiation using a UV solar simulator. The results showed that the OH photochemical formation rate is strongly related to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Photochemistry has also been implicated in the apparent photo‐production of condensed aromatics from non‐pyrogenic DOM (Chen et al ; Waggoner et al ) using photo‐irradiation experiments for samples with very high DOC and high iron content. Iron appears to play an important role in the cycling of DBC (Riedel et al ), and the presence of iron can induce photo‐flocculation of terrestrial DOM (Helms et al ; Sun and Mopper ). Therefore, the appearance of condensed aromatic structures in the particulate phase after photo‐irradiation of highly aromatic, high iron samples (Chen et al ) may have resulted from the photo‐flocculation of DBC already present in the water sample rather than the net production of condensed aromatic compounds.…”
Section: Degradative Processing and Environmental Sinks Of Dissolved mentioning
confidence: 99%
“…Photochemistry has also been implicated in the apparent photo‐production of condensed aromatics from non‐pyrogenic DOM (Chen et al ; Waggoner et al ) using photo‐irradiation experiments for samples with very high DOC and high iron content. Iron appears to play an important role in the cycling of DBC (Riedel et al ), and the presence of iron can induce photo‐flocculation of terrestrial DOM (Helms et al ; Sun and Mopper ). Therefore, the appearance of condensed aromatic structures in the particulate phase after photo‐irradiation of highly aromatic, high iron samples (Chen et al ) may have resulted from the photo‐flocculation of DBC already present in the water sample rather than the net production of condensed aromatic compounds.…”
Section: Degradative Processing and Environmental Sinks Of Dissolved mentioning
confidence: 99%
“…Fluorescence regional integration (FRI) is a new quantitative approach to analyze the total wavelength-independent fluorescence intensity data based on EEM spectra (Chen et al, 2003;Sun et al, 2016). EEM maps were divided into five regions, and a description of each region is provided in Table 1.…”
Section: Cdom Fluorescence Measurement and Fri Analysismentioning
confidence: 99%
“…Several studies on dissolved organic matter have shown that Fe takes part in the photo‐flocculation process (Gao and Zepp ; Helms et al ; Sun et al ). Iron not only accelerates ROS production, such as the Fenton reaction, but can also bind to organic ligands as complexes (Chen et al ; Sun and Mopper ). Recent studies by Waggoner et al () and Chen et al () have demonstrated, through molecular level analyses, that black‐carbon like macromolecules can be formed from terrestrial dissolved organic matter in the presence of sunlight and Fe.…”
Section: Background On the Study Of Marine Snow And Oil Spillsmentioning
confidence: 99%